Multidimensional approach to develop strategy map in small companies through BSC-AHP integration - Tonini Demuner, Matheus; Zatta, Fernando Nascimento; Freitas, Rodrigo Randow de; Gonçalves, Wellington (Brazilian Journal of Production Engineering, 2020)
The organizational strategy can be seen as a complex issue because it is a phenomenon composed of multiple variables, with components that have different priorities and different forms of management. And, for this reason, organizations need solutions that allow them to analyze their posture vis-à-vis the market, considering scenarios composed of several variables. This work aimed to propose an approach to analyze organizational performance in small companies, using the integration between the Balanced Scorecard (BSC) and the Analytic Hierarchy Process (AHP) to formulate a strategic map. The theoretical basis discussed on competitive strategies, the BSC and the AHP. The methodology used used a survey followed by a case study. The results suggest that the units of analysis (small companies in the furniture segment) are aligned with their strategies and indicators, the strategic map recommends that, in order to differentiate themselves, these units should invest in servitization and benchmarking.